Agenda 2030: Haunted by the Ghost of the Third Way?. Issue 1 (March 2018) - Güney-Frahm, Irem
Many thinkers in affluent countries consider the idea of the Third Way (TW) an outdated concept. This article argues that the concept of the TW still dominates the development discourse and as a consequence also influences policy prescriptions. Through a systematic examination of Human Development Reports (HDRs), the text shows that in the pre-2015 development agenda, the human development (HD) approach had significant similarities to the currents of thought that informed the TW. Second, the article analyzes the post-2015 development agenda and the HDR 2016, and shows that the Agenda 2030 flourishes on similar theoretical and practical premises as the TW and the pre-2015 agenda. Finally, the article discusses the shortcomings of this continuity.